Mandarin Chinese-speaking learners' acquisition of Italian consonant length contrast. (December 2022) - Feng, Qiang; Busà, M. Grazia
Abstract: The acquisition of Italian consonant length contrast by Mandarin Chinese-speaking learners (henceforth Chinese learners) has hardly been investigated. This study aims to fill this gap. Ten first-year, ten second-year and ten third-year Chinese undergraduate students majoring in Italian and ten native Italian-speaking controls took part in a perception and a production experiment. In the perception experiment, the participants had to identify ten Italian disyllabic minimal pairs contrasting in consonant length. In the production experiment, the participants were asked to read five out of the ten minimal pairs mentioned above; the duration values of the intervocalic consonants and the preconsonantal vowels were measured and converted into duration ratios for statistical analyses. The results show that, in both perception and production, Chinese learners can distinguish between the two consonant length categories in Italian to a certain extent, but not in a native-like manner. Also, the duration interplay between Italian consonants and preconsonantal vowels (i.e., longer vowels before singleton consonants and shorter vowels before geminate consonants) is entirely ignored by Chinese learners. Moreover, Chinese learners' increased learning experience does not appear to enhance their acquisition of Italian consonant length contrast. Some pedagogical implications are discussed.